(untitled) (Journal of Parents and Teachers, 2024)
The need to integrate family and school is emphasized in order to achieve a coherent education in the current context. Experiences in different educational centers (EP, ESO, BUP, COU, IP) are presented, highlighting the importance of collaboration and group work. In addition, a real coherence in educational approaches is sought to improve learning.